Behavior Genetics An International Journal Devoted to Research in the Inheritance of Behavior - Hewitt, John K.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Behavior Genetics - the leading journal concerned with the genetic analysis of complex traits - is published in cooperation with the Behavior Genetics Association. This timely journal disseminates the most current original research on the inheritance and evolution of behavioral characteristics in man and other species. Contributions from eminent international researchers focus on both the application of various genetic perspectives to the study of behavioral characteristics and the influence of behavioral differences on the genetic structure of populations. 5 Year Impact Factor: 3.411 (2007) Section "Psychology, Multidisciplinary": Rank 15 out of 101.
Keywords: Public health; Clinical psychology; Health psychology; Clinical Psychology; Health Psychology; Public Health